2018
DOI: 10.1007/s11356-018-2942-x
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of azo dye using core@shell nano-TiO2 particles to reduce toxicity

Abstract: Clean and safe water is fundamental for human and environmental health. Traditional remediation of textile dye-polluted water with chemical, physical, and biological processes has many disadvantages. Due to this, nano-engineered materials are drawing more attention to this area. However, the widespread use of nano-particles for this purpose may lead to photocatalytic degradation of xenobiotics, while increasing the risk of nano-particle-induced ecotoxicity. Therefore, we comparatively evaluated the toxicity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This is because each study is 'unique' in itself with respect to the scale of the assessment, the dye tested, the photocatalytic dye degradation conditions, the extents of degradation of the dye and degree of mineralization reached, the test subject(s) used to assess the toxicity levels and the specific architecture and chemical composition of the photocatalytic materials used (de Sousa Filho et al 2020;Serrà et al 2020). For example, recently, Ozmen et al (2018) reported several interesting findings when studying the photodegradation of disperse red 65 using core@shell nano-TiO 2 particles. Amongst the complete set of observations made in Ozmen et al (2018), the highlights comprised the following: (1) even at the maximum test concentration of core@shell NPs of 250 mg L −1 , there was little mortality in comparison with the control groups in Danio rerio and Xenopus laevis embryos, (2) the lower concentrations of NPs had not caused lethality to the embryos of the D. rerio and X. laevis species, (3) the prepared core@shell NPs had not brought about developmental abnormalities in the embryos, (4) however, an exposure to the photocatalytic degradation products of disperse red 65 obtained after 1 h of photodegradation led to 100% mortality in both test species after a 96-h exposure, (5) a photocatalytic degradation reaction lasting 2 h could partially lessen the lethal effect for X. laevis embryos, (6) 3 h of photocatalytic degradation of disperse red 65 had not led to mortality in the X. laevis embryos, viand in the case of D. rerio embryos, a 3-h photocatalytic degradation of disperse red 65 using the synthesized TiO 2 and SiO 2 @ TiO 2 catalysts had eliminated the lethal effects of disperse red 65 on the zebrafish embryos.…”
Section: Biocompatibility and Ecotoxicological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because each study is 'unique' in itself with respect to the scale of the assessment, the dye tested, the photocatalytic dye degradation conditions, the extents of degradation of the dye and degree of mineralization reached, the test subject(s) used to assess the toxicity levels and the specific architecture and chemical composition of the photocatalytic materials used (de Sousa Filho et al 2020;Serrà et al 2020). For example, recently, Ozmen et al (2018) reported several interesting findings when studying the photodegradation of disperse red 65 using core@shell nano-TiO 2 particles. Amongst the complete set of observations made in Ozmen et al (2018), the highlights comprised the following: (1) even at the maximum test concentration of core@shell NPs of 250 mg L −1 , there was little mortality in comparison with the control groups in Danio rerio and Xenopus laevis embryos, (2) the lower concentrations of NPs had not caused lethality to the embryos of the D. rerio and X. laevis species, (3) the prepared core@shell NPs had not brought about developmental abnormalities in the embryos, (4) however, an exposure to the photocatalytic degradation products of disperse red 65 obtained after 1 h of photodegradation led to 100% mortality in both test species after a 96-h exposure, (5) a photocatalytic degradation reaction lasting 2 h could partially lessen the lethal effect for X. laevis embryos, (6) 3 h of photocatalytic degradation of disperse red 65 had not led to mortality in the X. laevis embryos, viand in the case of D. rerio embryos, a 3-h photocatalytic degradation of disperse red 65 using the synthesized TiO 2 and SiO 2 @ TiO 2 catalysts had eliminated the lethal effects of disperse red 65 on the zebrafish embryos.…”
Section: Biocompatibility and Ecotoxicological Implicationsmentioning
confidence: 99%
“…For example, recently, Ozmen et al (2018) reported several interesting findings when studying the photodegradation of disperse red 65 using core@shell nano-TiO 2 particles. Amongst the complete set of observations made in Ozmen et al (2018), the highlights comprised the following: (1) even at the maximum test concentration of core@shell NPs of 250 mg L −1 , there was little mortality in comparison with the control groups in Danio rerio and Xenopus laevis embryos, (2) the lower concentrations of NPs had not caused lethality to the embryos of the D. rerio and X. laevis species, (3) the prepared core@shell NPs had not brought about developmental abnormalities in the embryos, (4) however, an exposure to the photocatalytic degradation products of disperse red 65 obtained after 1 h of photodegradation led to 100% mortality in both test species after a 96-h exposure, (5) a photocatalytic degradation reaction lasting 2 h could partially lessen the lethal effect for X. laevis embryos, (6) 3 h of photocatalytic degradation of disperse red 65 had not led to mortality in the X. laevis embryos, viand in the case of D. rerio embryos, a 3-h photocatalytic degradation of disperse red 65 using the synthesized TiO 2 and SiO 2 @ TiO 2 catalysts had eliminated the lethal effects of disperse red 65 on the zebrafish embryos. Serrà et al (2020) recently reported a significant enhancement in algal viability when using supported ZnO@ZnS core@shell micro/nanoferns after noting that the corresponding ecotoxicity after a 96-h light exposure was considerably lower in comparison with the ZnO films, ZnO NPs, ZnO micro/nanoferns or ZnO@ ZnS NPs at concentrations ranging from 25 to 400 mg L −1 .…”
Section: Biocompatibility and Ecotoxicological Implicationsmentioning
confidence: 99%
“…[178][179][180][181][182][183][184] Many chemical industry dyes were especially toxic and were known to increase the risk of illness. [185][186][187][188][189][190][191][192] Adsorption has been considered to be a green method in removing these pollutants due to the high efficiency, easy operation, and low cost. [193][194][195][196][197] COFs and MOFs as well-known porous materials have been applied in the field of pollutant adsorption.…”
Section: Pollution Adsorptionmentioning
confidence: 99%
“…Photocatalysis is a promising, clean process that can be applied in the degradation of persistent organic pollutants, such as organic dyes [ 1 , 2 , 3 , 4 , 5 , 6 ]. This process initiates with the irradiation of a suitable catalyst’s surface with a type of radiation, i.e., UV, visible, or solar, with energy equal to or higher than the bang gap energy (E g ) value.…”
Section: Introductionmentioning
confidence: 99%